Security Infrastructure for Hybrid Clouds and Cloud Federation. Issue 2 (2014) - Sitaram, Dinkar; Phalachandra, H. L.; Vishwanath, Anush; Ramesh, Pramod; Prashanth, Meghana; Joshi, Akshay G.
No abstract available